Study of the health status of geriatric age group in Chitwan district of Nepal - Subedi, L; Sah, R B (Journal of Chitwan Medical College, 2015)
Retirement, change in housing, illness or death of spouse greatly affect the physical and mental well-being of the geriatric person. This study aims to find out the health status of geriatric age group in chitwan district of Nepal. A cross sectional study was carried out among 300 geriatric people where 15.7% of the geriatric were living alone, 50.3 % and 39.7% of geriatrics gave history of regular use of tobacco and alcohol respectively. Co-morbidities were found in 63% of geriatrics who suffered from 2 or more diseases. In Total 44% were found to have Ophthalmic problems, 23% were found to have ENT problems, 5.33% were found to mental disorders, 33% were found to have CVS problems, 43% were found to have GI problems, 15.67 % were found to have Metabolic disorder. The study highlighted a high prevalence of morbidity and health related problems in geriatric age groups. DOI: http://dx.doi.org/10.3126/jcmc.v5i1.12560